Bede and the end of time - Darby, Peter (Studies in early medieval Britain, 2012)
Chronology and the world ages in De temporibus -- The Epistola ad pleguinam and its contemporary setting -- The expanded world ages scheme -- Signs, portents and the end-time sequence -- The day of judgement and the eternal afterlife -- Bede's eschatological perspective and Gregory the Great -- Bede's eschatological perspective in the Crisis of 716 -- Bede's eschatological perspective: the wider context